The Use of PLEASE Strategy in Teaching Writing Descriptive Text for the Tenth Grade - Mahdiyah Mahdiyah; Lestari Siti; Sukma Nur Ardini (Universitas Majalengka, 2020)
The paper aimed at finding out the significant different between the students’ writing skill taught with and without using PLEASE strategy. The researchers used quasi-experimental research with two groups. The population of the research was the tenth grade students of SMKN Jenawi. The researchers took two classes as experimental class and control class. The researchers gave post-test only for each class and the treatment to the experimental class. To collect the data, the researchers used essay test. The mean of the post-test in experimental class was 83.5 and the mean of the post-test of control class was 62.3. Then the result was calculated quantitatively using SPSS. It showed that there were any significant difference. The researchers concluded that PLEASE strategy can improve students writing descriptive text. Eventually, pedagogical implication of the research, hopefully, can be used as a supplementary reference with different discussion.